2018
DOI: 10.1002/slct.201702976
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Assisted Rhodium Catalyzed Selective Semi‐hydrogenation of Alkynes Using Syngas and Molecular Hydrogen

Abstract: This work reports the Rhodium catalyzed selective semi‐hydrogenation of alkynes to (E) and (Z)‐alkenes in the presence of various Buchwald phosphine ligands such as S‐Phos (L1), t‐Bu XPhos (L2), Ru‐Phos (L3), Johnphos (L4) and DavePhos (L5). Selective formation of E‐alkenes in high activity with use of H2 gas (5 bar) is an alternative method for conventional Birch reduction. High selectivity obtained towards Z‐alkenes with use of syngas (10 bar) is an alternative method for Lindlar reaction. (E)‐alkenes were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…To date, several homogeneous catalytic systems have been developed for semihydrogenation of alkynes. The transition metals involved in these systems are Pd, Ru, Rh, Ir, V, Ni, Co, Cu, Mn, and even Fe . Despite these significant achievements, many of the above mentioned procedures face limitations, such as lengthy synthesis process for catalysts, elevated reaction temperature, by‐product formation due to over‐reduction, and tedious operation of H 2 usage.…”
Section: Methodsmentioning
confidence: 99%
“…To date, several homogeneous catalytic systems have been developed for semihydrogenation of alkynes. The transition metals involved in these systems are Pd, Ru, Rh, Ir, V, Ni, Co, Cu, Mn, and even Fe . Despite these significant achievements, many of the above mentioned procedures face limitations, such as lengthy synthesis process for catalysts, elevated reaction temperature, by‐product formation due to over‐reduction, and tedious operation of H 2 usage.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, H + /H – pairs tend to kinetically reduce polar groups, which greatly improves the chemical selectivity of hydrogenation. 26 For example, Zheng’s group found that the Pd/Cu 2 O catalyst showed excellent performance for semihydrogenation of terminal alkynes. This was mainly because the unique interface structure of Pd/Cu 2 O and Pd 1+ promoted the heterolysis of H 2 at Pd–O–Cu sites.…”
Section: Advantages Of Pd-based Catalysts and The Factors Influencing Their Catalytic Performancementioning
confidence: 99%
“…Due to the noncompetitive adsorption of the substrate and H 2 , there is sufficient space for the activation of H 2 . Besides, H + /H – pairs tend to kinetically reduce polar groups, which greatly improves the chemical selectivity of hydrogenation . For example, Zheng’s group found that the Pd/Cu 2 O catalyst showed excellent performance for semihydrogenation of terminal alkynes.…”
Section: Advantages Of Pd-based Catalysts and The Factors Influencing...mentioning
confidence: 99%
“…Selective hydrogenation of alkynes such as phenylacetylene (PA) to styrene (ST) constitutes a great significance in both industry and scientific research [1–4] . It is an effective method to remove the by‐product during the production process of polyethylene and polystyrene [5,6] .…”
Section: Introductionmentioning
confidence: 99%